Analysis of in vitro demineralised human enamel using multi-scale correlative optical and scanning electron microscopy, and high-resolution synchrotron wide-angle X-ray scattering - Besnard, C; Harper, RA; Salvati, E; Moxham, TEJ; Brandt, LR; Landini, G; Shelton, RM; Korsunsky, AM (Elsevier, 2021)
Enamel caries is a highly prevalent worldwide disease that involves the demineralisation of the outer tooth structure. In this study, we report the analysis of artificially demineralised human enamel sections (‘slices’) etched using lactic acid (2% v/v) in comparison with healthy enamel using correlative techniques of optical and electron microscopy, as well as scanning diffraction. Demineralisation of the enamel was characterised at the micron to sub-micron scale. The structure of the healthy enamel was investigated using Focused Ion Beam - Scanning Electron Microscopy (FIB-SEM) and compared with an etched sample to reveal their structural differences. Additional chemical analysis using energy-dispersive X-ray spectroscopy (EDS) was performed and a decrease in the Ca/P atomic % ratio was found in etched samples in comparison with healthy enamel, suggesting greater loss of calcium compared with phosphorus. Synchrotron wide-angle X-ray scattering (WAXS) was performed on the samples to reveal the differences in the diffraction patterns before and after etching in terms of lattice structure and preferred orientation (texture). Texture maps were extracted from diffraction analysis at 500 nm spatial resolution. These maps were correlated with the dimension of the enamel structure. The multi-scale correlative approach provided insights into the demineralisation-induced enamel structure alteration at a resolution approaching 500 nm.